Simulation of fire resistance of reinforced concrete structural members - Lakhani, Hitesh; Kamath, Praveen; Bhargava, Pradeep; Singh, Tarvinder; Reddy, G.R. (Journal of Structural Engineering, 2024)
A sequentially coupled thermal stress analysis is carried out using finite element analysis package, ABAQUS. Comparisons of different thermal analysis results have been made with focus on the effect of the boundary conditions (BC). Two types of BC’s were used to simulate the heat transfer from surrounding air to the structural member during fire. Former is comparatively simplified prescribed temperature BC and second is convection and radiation BC which involves more parameters. The thermal and mechanical results obtained were compared with experimental results, which served as a validation of the modeling approach and properties.